Tolerance of Melon (Cucumis melo L.) Cultivar Melodi Gama 3 to Powdery Mildew Infection - Rozikin, Rozikin; Daryono, Budi Setiadi (Universitas Labuhanbatu, 2023)
Powdery mildew is one of melon disease caused by ascomycetes fungus from genus Sphaerotheca and Erysiphe. Breeding is considered to be the best approach to control Powdery mildew infection especially in melon. MG3 is a melon cultivar derived from ‘MG1’ x ‘Ladika’ and its estimate carry out resistant gene to Powdery mildew infection inherited from MG1. This research is to find out percentage and phenotype characters of Powdery mildew infection in MG3 compared to four commercial melons (Action 434, Glamour, MAI and ladika) that are popular in the market. Five melons are planted in greenhouse B of KP4 UGM. After five weeks, the plants where inoculated with Powdery mildew KP4 UGM in leaves. Scoring in three days after inoculation and the percentage of infections measured every 3 days for eight times using grid line 21 cm x 21 cm with small cubics 1,5 cm x 1,5 cm. The analysis of infections level in leaves, plant and population was done using Fukino protocol. The results show that cultivar MG3 tolerant and stable to Powdery mildew infection compare to cultivar Action 434, MAI and ladika in leaves, plant and population level. The infection of Powdery mildew caused damage to the leaves tissue, decreasing the abilities of photosynthesis resulting in necrotic, chlorotic and dead of the infected leaves. In fruits, infection causes break in the net, immature and rotten flesh, decrease sweetness and scent in cultivar Action434, MAI and Ladika. Base on microscopic analysis, Powdery mildew isolat KP4 UGM is a member of from genus Podosphaera.